Comparative Evaluation of Classical Inferior Alveolar Nerve Block and Gow-Gates Nerve Block for Surgical Removal of Mandibular Third Molar: IANB vs Gow-Gates for Mandibular Third Molar Surgery - Khan, Muhammad Mohsin; Ilyas, Muhammad; Sheikh, Taha; Sohail, Aaisha; Ahmad, Syeda Sidra; Khalid, Fahad (Pakistan Journal of Health Sciences, 2026)
Effective anesthesia is essential for the surgical removal of mandibular third molars. While the classical inferior alveolar nerve block is widely used, its success may be limited by anatomical variations. The Gow-Gates technique is considered a potential alternative offering broader mandibular anesthesia. Objectives: To evaluate and compare the classical inferior alveolar nerve block and Gow-Gates nerve block for surgical removal of mandibular third molars in terms of Anesthetic success rate, Onset and duration of anesthesia, and patient-reported pain using a visual analog scale. Methods: A quasi-experimental, comparative study was performed in which a total of 160 patients were selected and randomly allocated to receive Gow-Gates (GG) nerve block or inferior alveolar nerve block (IANB) for the extraction of mandibular molars. Onset time, pain levels, and volume of anesthesia were recorded as data. SPSS statistical analysis version 26.0 was used for data analysis. Results: Regarding gender, females were counted more, 87, comprised 54.43 % of the sample, whereas 73 men accounted for 45.57 %. The onset time of the Gow-Gates group took 6.16 minutes, which is slower than IANB, 2.78 minutes; however, the success rate of both techniques is about the same, 87.5%. Furthermore, the mean volume of local anesthesia used to anesthetize tissues was higher in the IANB group than in the GG group. Conclusions: Both methods are useful in mandibular anesthesia, and Gow-Gates has a high rate of success and less chance of aspiration, though IANB has a quicker onset. Patient and clinician factors determine the technique to be used.